M&A: The case of Optimus and Zon - Almeida, Margarida de Lagos Vian Correia de (2014)
On the course of this thesis it is proposed to find and point out the reasons that may had led Sonaecom/Optimus and Zon merger to be postponed until now, even though this operation seemed to have a profitable potential and that it was supported by different organizations, such as the competition authority and the national telecommunications sector. Throughout this study, one will try to find out and point out the reasons that may determine or influence in any way a merger or an acquisition to be successful or not. I will also try to explain what will be different in the case of the proposal between Optimus and Zon, from the previous attempts, and especially if there was a governance problem. Such problem may have affected previous negotiations and it can also affect the future of the merger. It is proposed to understand up to what point this issues may be relevant in this case. During this thesis other questions will also be addressed, namely the importance of this operation to stimulate new dynamics in mergers and acquisitions in Portugal. Through this dissertation it was found that this merger is expected to have benefits for both companies’ shareholders and the postponing of this operation seems to be a clear governance problem. It will be crucial to understand if there is a leadership capable of materializing the expected gains for the companies, the shareholders and the market itself. This operation could have a positive consequence on the market itself if it would create a stimulus for other similar operations to happen.